Understanding Digital Literacy Culture in Students (Analytical study on PGSD students at Universitas Muhammadiyah Cirebon) - Faiz, Aiman; Purwati; Suryangi, Ramadhan Achmad; Sutanto, Himawan; Jundulloh, Muhamad Fikri (PT Inovasi Pratama Internasional, 2024)
The aim of this research is to analyze the extent to which students are able to utilize digital literacy. This research uses a descriptive study method with a qualitative approach. The data collection technique uses the results of a questionnaire created using a Google form which is distributed to students. The results of this research show that students of the PGSD study program at Muhammadiyah University of Cirebon have excellent digital literacy skills in using information and digital technology facilities. Digital literacy provides PGSD students at Muhammadiyah University of Cirebon with the opportunity to expand their knowledge by obtaining concrete data sources. By understanding and applying digital skills, becoming more innovative and creative, gaining experience with technology in college and in the future. Based on the results of data processing and data presentation, it can be concluded that students of the PGSD study program at Muhammadiyah University, Cirebon have excellent digital literacy skills in using information and digital technology facilities. Although there is something lacking in using digital literacy to retrieve information media.